Improving Students' Narrative Understanding of Fractured Fairy Tale Material Through The Picture and Picture Method in Class X-I SMAN 2 Pamekasan - Noroniyah, Alvin; Maimuna, Maimuna; Putri, Hilmalia; Ibana, Lukluk; Ulfa, Maria; Agustien, Liza (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve students' ability to interpret narrative texts, especially in fractured fairy tale materials, through the application of the picture-picture method. The subjects of this study were students in class X-I SMAN 2 Pamekasan, with a total of 36 students. The method used is class action research (PTK) which is carried out in cycle II. Each cycle consists of the following stages: plannig, acting, observing, reflecting. The results of the pre-cycle stage showed that the average student score reached only 60, with a completion rate of 30%. After the actions in cycle I were implemented, the average increased to 65 with a completion percentage of 50%. In cycle II, student learning outcomes have increased significantly, with an average score of 80 and learning completeness increasing to 86.11%. This improvement shows that the picture and picture method is effective in helping students understand the content and storyline through visualization of images arranged sequentially. This method not only makes students more active and interested in the learning process, but also proven to be able to improve student learning outcomes in real terms